EXTRACELLULAR ALKALINE PROTEASE PRODUCING HALO-ALKALITOLERANT BACTERIA ISOLATED FROM MARINE COASTS OF ODISHA - Maharana, Abhas Kumar; Sinha, Ishita; Behera, Prakash Chandra; Ray, Pratima (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of the present study was on the isolation of alkali-tolerant bacteria from sediment samples of different coasts of Odisha, having potentiality to produce alkaline protease. Methods: About 25 sediment samples were collected and analyzed for pH and moisture contents. Then isolation of alkali-tolerants was done using Horikoshi media at 10.3 pH. Isolates were analyzed for producing alkaline protease by plate assay method both at pH 6 and 10. Effects of temperature on protease production were also determined. Besides a new method of quantification of enzymes were adapted. Along this the isolates were partially characterized and identification was done using PIBWin software. Results: About 80 isolates were initially isolated, and 11 isolates were considered based on maximal zones of clearances at alkaline pH. Maximum solubilisation index (SI) was found to be 30 mm by 3 isolates viz. AP2, AP8 and AP13 while maximum hydrolytic run percentage (HR%) was found to be 65.39% by AP3. About 45.46% isolates had capability for protease production at 37 °C and 18.18% at 57 °C while 81.82% isolates showed production at 17 °C. AP8 was the good producers of alkaline protease having SI 39 mm at pH 10 while incubating at 47 °C. Isolates were characterized partially by cultural, morphological, biochemical and physiological tests, which were belonged to the genera of Bacillus, Virgibacillus and Micrococcus. The isolated bacteria showed growth at pH ranges from 4-12 and can tolerate 12% NaCl concentrations for their growth. Conclusion: Due to the above unique features and capability to produce alkaline proteases by the marine isolates, can be used significantly in various industries. Keywords: Alkali-tolerant, Alkaline protease, Halo-tolerant, Hydrolytic run, Odisha-coast